Utility Function for modeling Group Multicriteria Decision Making problems as games - Alexandre Bevilacqua Leoneti (Operations Research Perspectives, 2016)
To assist in the decision making process, several multicriteria methods have been proposed. However, the existing methods assume a single decision-maker and do not consider decision under risk, which is better addressed by Game Theory. Hence, the aim of this research is to propose a Utility Function that makes it possible to model Group Multicriteria Decision Making problems as games. The advantage of using Game Theory for solving Group Multicriteria Decision Making problems is to evaluate the conflicts between the decision makers using a strategical approach.
Keywords: 330; Utility function; Group Multicriteria Decision; MAUT; Game Theory